Comparison of conventional risk factors, clinical and angiographic profile between younger and older coronary heart disease patients - Khadkikar, Gajanan D.; Mangudkar, Sangram S.; Landge, Jyoti A. (International Journal of Research in Medical Sciences, 2016)
Background: Although numerous risk factors have been established to predict the development of Coronary artery Disease, the risk factor profile may be different between the younger and older individuals. The aim of the study was to compare risk factors, clinical profile and angiographic profile of young and old coronary heart disease patients. Methods: Patients admitted at cardiac intensive care unit at Sunderam Ahulraj Hospital of south India between January 2012 and December 2013 were classified in to two age groups with 40yrs as cut-off. Patients were assessed for conventional risk factors (diabetes mellitus, dyslipidaemia, hypertension, smoking, and obesity), clinical profile and angiographic profiles. Results: A total of 100 patients, out of which 32patients were ≤40yrs of age and 68 patients >40yrs of age, were evaluated. Mean age for younger group (<40yrs) was 33.56 yrs and for older (>40yrs) was 55.39 yrs. Range of age group for study population was 28-72 yrs. The prevalence of obesity, dyslipidaemia, and smoking/ tobacco chewing did not vary significantly between the two groups. Older patients had higher frequency of diabetes (48.5%) and hypertension (41.1%). The most commonly affected coronary artery was the left anterior descending artery among both age groups. Conclusions: Young patients with Coronary heart disease had different risk profile and less extensive coronary artery disease as compared to older counterparts. Emphasis should be given on diagnosis and management of major modifiable risk factors.